Educational interventions on nutrition among older adults: A systematic review and meta-analysis of randomized clinical trials. (June 2020) - Neves, Felix Jesus; Tomita, Luciana Yuki; Liu, Angela Sun Li Wu; Andreoni, Solange; Ramos, Luiz Roberto
Highlights: Interventions to increase fruit and vegetable intake were effective. The largest effect size was observed for interventions with vegetable intake. Interventions based on fruit and vegetables also increased fibre intake. Abstract: Poor nutrition is a major risk factor for non-communicable diseases and nutritional deficiencies. Dietary interventions have been proposed to improve eating habits. The aim of this systematic review is to evaluate the efficacy of randomized clinical trials of nutritional interventions in food habits among older people. A systematic literature review using the MEDLINE, LILACS, Scopus, Cochrane Library, Web of Science and Google Scholar databases was conducted, according to PRISMA guidelines. The keywords were: food and nutrition education OR educación alimentaria y nutricional OR educação alimentar e nutricional AND clinical trial OR ensayo clínico OR ensaio clínico AND elderly OR aged OR anciano OR idoso AND human OR seres humanos. The pooled standardized mean differences (SMD) and 95 % confidence intervals (CIs) were estimated using a random-effects model. Heterogeneity among studies was assessed using I² tests. After screening based on the title and abstract, and a full-text assessment, 11 studies remained. Results of pooling eleven studies were as follows: SMD = 0.25 (95 % CI = 0.15 – 0.34; I² = 0, 0%) for vegetable, SMD = 0.18 (95 % CI = 0.08 – 0.27; I² = 0, 0%) for fruit and SMD = 0.27 (95 % CI = 0.18 – 0.36; I² = 58, 3%) for fibre intake. Our results suggest that nutritional interventions were effective in increasing vegetable, fruit and fibre intake. However, these results should be analyzed carefully, due to the small number of studies included in the meta-analysis. Further studies should be encouraged due to the aging process.